No Association of Gaucher Disease With COVID-19 Outcomes: A Nationwide Cohort Study - Demirci, Ibrahim; Demir, Tevfik; Dagdelen, Selcuk; Haymana, Cem; Tasci, Ilker; Atmaca, Aysegul; Sonmez, Alper (Wiley, 2022)
Background It is well documented that patients with chronic metabolic diseases, such as diabetes and obesity, are adversely affected by the COVID-19 pandemic. However, when the subject is rare metabolic diseases, there are not enough data in the literature. Aim To investigate the course of COVID-19 among patients with Gaucher disease (GD), the most common lysosomal storage disease. Methods Based on the National Health System data, a retrospective cohort of patients with confirmed (polymerase chain reactionpositive) COVID-19 infection (n = 149 618) was investigated. The adverse outcomes between patients with GD (n = 39) and those without GD (n = 149 579) were compared with crude and propensity score-matched (PSM) groups. The outcomes were hospitalisation, the composite of intensive care unit (ICU) admission and/or mechanical ventilation and mortality. Results The patients with GD were significantly older and had a higher frequency of hypertension (HT), Type 2 diabetes mellitus (T2DM), dyslipidaemia, asthma or chronic obstructive pulmonary disease, chronic kidney disease, coronary artery disease, heart failure and cancer. Although hospitalisation rates in Gaucher patients were found to be higher in crude analyses, the PSM models (model 1, age and gender matched; model 2, matched for age, gender, HT, T2DM and cancer) revealed no difference for the outcomes between patients with GD and the general population. According to multivariate regression analyses, having a diagnosis of GD was not a significant predictor for hospitalisation (P = 0.241), ICU admission/mechanical ventilation (P = 0.403) or mortality (P = 0.231). Conclusion According to our national data, SARS-CoV-2 infection in patients with GD does not have a more severe course than the normal population.
Celik, Osman/0000-0003-2131-2866; Cakal, Erman/0000-0003-4455-7276; Demirci, Ibrahim/0000-0003-0498-3115; Tasci, Ilker/0000-0002-0936-2476; Sahin, Mustafa/0000-0002-4718-0083;
Keywords: Gaucher; Coronavirus; COVID-19; SARS-CoV-2; Mortality; National